Synchronous primary malignancy of head and neck- a case report - Ramasamy, Maheswari; G V, Manoharan; Narayanasamy, Sangara Narayanan (International Journal of Research in Medical Sciences, 2017)
The incidence of multiple primary malignant neoplasms increases with age, reflecting an increase in overall cancer risk in older patients. Cases of two or more concurrent primary cancers are still rare, although its incidence is increasing. Here, we report the case of a 41-years female who was referred to our institution with synchronous papillary carcinoma of thyroid and Adenoid cystic carcinoma of submandibular gland. The case is being presented to emphasize that the clinicians should keep in mind that the appearance of another tumour in a patient suffering from cancer could be either a synchronous or a metachronous or a metastatic lesion.